Sacarificação e isomerização simultâneas de dextrina na produção de xarope de frutose por ação sinérgica de CLEAs magnéticos de amiloglicosidase e Sweetzyme® - Fonseca, Murilo Amaral (Universidade Federal de São Carlos, 2019)
High fructose syrup is a sweetener widely used as a substitute for sucrose by the food and beverage industry. It has many advantages such as relative sweetness superior to sucrose, high solubility, crystallization resistance and humectant action. Its current industrial production is by enzymatic route basically occurring in three processes: liquefaction, saccharification and isomerization, by the action of the enzymes α-amylase, amyloglucosidase (AMG) and glucose isomerase (GI), respectively. Due to the fact that these enzymes are conducted under different conditions, all three processes are sequential, requiring time, equipment, and reagents for pH adjustment. Moreover, the enzymes α-amylase and amyloglucosidase are applied in a soluble form, limiting their use to batch operations. Due to its considerable industrial interest, glucose isomerase is marketed in its immobilized form. In the search for alternatives to increase productivity and efficiency of processes with lower operating costs, the aim of this research is to study the application of a simultaneous saccharification and isomerization process that could be operated repeatedly, reusing the biocatalysts employed. In order to develop this simultaneous multi-enzymatic process, initially it would be necessary to immobilize the AMG in order to make it insoluble and operationally more stable. The preparation of cross-linked enzyme aggregates (CLEA) is a simple, cost-effective and carrier-free technique capable of generating insoluble biocatalysts with high volumetric activity and improved stability. Its preparation consists of enzyme aggregation by precipitation and its subsequent cross-linking with a bifunctional agent. In this study, the CLEAs of AMG were prepared co-aggregated in the presence of polyethyleneimine (PEI) and/or starch, with aminated magnetic nanoparticles (MNPs) or bovine serum albumin (BSA), in order to improve the properties of the catalyst. The CLEAs prepared only with MNPs at different glutaraldehyde concentrations yielded a recovered activity of around 20%. The addition of starch or PEI increased the recovered activity around twofold (40%). Moreover, under the same conditions, AMG co-aggregated with BSA was also synthesized, yielding CLEAs with very similar recovered activity. Both CLEAs (co-aggregated with MNPs or BSA) were four times more stable than the soluble enzyme. These CLEAs were also evaluated in the hydrolysis of starch at 35% (w/v), achieving more than 95% starch-to-glucose conversion measured as Dextrose Equivalent (DE). Besides, both CLEAs could be reused for five cycles maintaining a DE of around 90%. Although both CLEAs had good properties, magnetic CLEAs could be more attractive because of their easy separation by an external magnetic field. Having the immobilized biocatalysts (AMG CLEA and GI) it was possible to work in a wider operational window, allowing the application of a factorial design with a central composite rotatable design, which was able to define an optimum pH and process temperature condition, as well as the best relation between the two enzymes. Simultaneous saccharification and isomerization from a dextrin solution 35% (w/v) reached a DE above 95%, with conversion yields around 48% of fructose at the end of 30 h of reaction. In addition, the catalysts could be reused for six consecutive cycles, maintaining conversion yields around 47% of fructose without loss of activity and with easy recovery of the biocatalysts. Furthermore, because they are of different natures (magnetic CLEA of amyloglucosidase and pellets of GI), if there is any inactivation of one of the biocatalysts, they could be easily separated and recharged individually.
Simultaneous saccharification and isomerization of dextrin in the production of fructose syrup by synergic action of magnetic CLEAs of amyloglucosidase and Sweetzyme®
Keywords: Xarope rico em frutose; Sacarificação e isomerização simultânea; Agregados de enzima entrecruzados; Amiloglicosidase; Glicose isomerase; High fructose syrup; Simultaneous saccharification and isomerization; Cross-linked enzyme aggregate; Amyloglucosidase; Glucose isomerase; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA